Tabuik is a Legendary Icon of the Pariaman Community who has Emerged as a Leader in the Economic Sector - Dilta, Salsa Yusari; Erianjoni, Erianjoni (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2024)
Tabuik, a traditional event in Pariaman, has become an emblematic symbol of West Sumatera’s regional identity. However, its contemporary implementation has shifted its focus from a cultural celebration to a promotional tool aimed at bolstering the local economy. Drawing upon Anthony Giddens’ agency structuration theory, this research elucidates the mutually reinforcing dynamic between agents and structures. The agents in this context encompass the government and traditional groups, whose interactions shape the structure and practices of Tabuik. The research employs Miles and Huberman’s data analysis techniques, encompassing data collection, reduction, presentation, and verification. The findings reveal a transformation in the sacred values associated with Tabuik. This shift was catalyzed by the government’s efforts to suppress Shi’ite influences perceived as detrimental to societal stability and its interpretation of Tabuik as a Shi’ah teaching. Subsequently, Tabuik gained recognition as a tourist attraction, contributing to the community’s economic development by drawing both domestic and foreign visitors. The enduring significance of Tabuik as a local wisdom in Minangkabau, coupled with its status as an icon and global recognition, has had a profound impact on various communities. It has become a draw for tourists, both domestic and international, contributing to the region’s economic growth. The research concludes that Tabuik, a tradition that has endured for decades, has adapted to contemporary developments, particularly in the context of the 5.0 era.